At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
(-1, 3)
Step-by-step explanation:
to solve using substitution, you have to know the value of either x or y. in this example, they gave you the value of y already: y=x+4.
this means you can substitute the y for (x+4). if we substitute y for (x+4) in the equation y=-5x-2, we get this:
(x+4)=-5x-2
then solve for x
6x=-6
so x=-1
since we know the x value, we can solve for y
y=x+4
y=-1+4
y=3
so the final answer is (-1, 3)
Answer:
(- 1, 3 )
Step-by-step explanation:
Given the 2 equations
y = x + 4 → (1)
y = - 5x - 2 → (2)
Substitute y = x + 4 into (2)
x + 4 = - 5x - 2 ( add 5x to both sides )
6x + 4 = - 2 ( subtract 4 from both sides )
6x = - 6 ( divide both sides by 6 )
x = - 1
Substitute x = - 1 into either of the 2 equations and evaluate for y
Substituting into (1)
y = - 1 + 4 = 3
solution is (- 1, 3 )
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.